Misplaced Cu-T as a Cause of Recurrent Urinary Tract Infection - A Rare Case (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Abstract not availableBangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 107-110